2004
DOI: 10.1021/ja049050k
|View full text |Cite
|
Sign up to set email alerts
|

[Fe2(SR)2(μ-CO)(CNMe)6]2+ and Analogues:  A New Class of Diiron Dithiolates as Structural Models for the HoxAir State of the Fe-Only Hydrogenase

Abstract: Low-temperature oxidation of Fe(2)(S(2)C(n)H(2n)(CNMe)(6-x)(CO)x (n = 2, 3; x = 2, 3) affords a family of mixed carbonyl-isocyanides of the type [Fe(2)(S(2)C(n)H(2n)(CO)x(CNMe)(7-x)](2+). The degree of substitution is controlled by the RNC/Fe ratio, as well as the degree of initial substitution at iron, with tricarbonyl derivatives favoring more highly carbonylated products. The structures of the monocarbonyl derivatives [Fe(2)(S(2)C(n)H(2n))(mu-CO)(CNMe)(6)](PF(6))(2) (n = 2,3) established crystallographicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 63 publications
5
85
0
Order By: Relevance
“…Recently, Pickett and co-workers have reported their assembly by linking of an [Fe 4 S 4 ] cluster to a diiron unit, which offers the prospect of understanding the catalytic mechanisms of [Fe]H 2 ases. [26] Rauchfuss et al have developed syntheses of mixed-ligand diferrous dithiolate complexes by the oxidative decarbonylation of diiron dithiolates, [27,28] and Darensbourg and co-workers have described the electrocatalytic production of H 2 by PDT-bridged diiron derivatives [(µ-PDT)Fe 2 (CO) 4 (PR 3 ) 2 ] in the presence of the weak acid HOAc. [29,30] Rauchfuss et al have demonstrated that the mixed-ligand substituted diiron system [(µ-PDT)Fe 2 (CO) 4 PMe 3 (CN)] -is an electrocatalyst for H 2 production with the strong acid p-toluenesulfonic acid (HOTs).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Pickett and co-workers have reported their assembly by linking of an [Fe 4 S 4 ] cluster to a diiron unit, which offers the prospect of understanding the catalytic mechanisms of [Fe]H 2 ases. [26] Rauchfuss et al have developed syntheses of mixed-ligand diferrous dithiolate complexes by the oxidative decarbonylation of diiron dithiolates, [27,28] and Darensbourg and co-workers have described the electrocatalytic production of H 2 by PDT-bridged diiron derivatives [(µ-PDT)Fe 2 (CO) 4 (PR 3 ) 2 ] in the presence of the weak acid HOAc. [29,30] Rauchfuss et al have demonstrated that the mixed-ligand substituted diiron system [(µ-PDT)Fe 2 (CO) 4 PMe 3 (CN)] -is an electrocatalyst for H 2 production with the strong acid p-toluenesulfonic acid (HOTs).…”
Section: Introductionmentioning
confidence: 99%
“…Particular emphasis has been placed on variations of L, especially tertiary phosphines [1][2][3], but also isocyanides [4,5], N-heterocyclic carbenes [6][7][8][9], and cyanide [10][11][12][13]. While much effort has focused on functionalizing the dithiolate ligand [14][15][16][17][18][19][20], relatively little work has examined the possibility of replacing the thiolates with other bridging groups [21].…”
Section: Fe Complexes; Metal Hydride; Hydrogenase; Electrocatalysismentioning
confidence: 99%
“…A stable monocyanide derivative was prepared via the reaction of 1 with KN(SiMe 3 ) 2 [11]. Similarly, treatment of 1 with Me 3 NO gave the MeCN complex Fe 2 (BC)(CO) 5 (MeCN) (ν CO = 2043CO = , 2030CO = , 1976CO = , 1964CO = , 1913 cm −1 ) [29], which was found to react with Et 4 NCN to afford Et 4 N[Fe 2 (BC) (CO) 5 (CN)], as indicated by IR spectroscopy and ESI-MS. 2 It was of interest to determine if the diiron azo system 2 could be protonated at the Fe-Fe bond and, if so, would the resulting hydride electrocatalyze proton reduction, analogous to the reactivity observed in Fe 2 (SR) 2 systems [29][30][31]. Indeed, we found that HCl effected protonation at the Fe-Fe bond of 2, thereby forming a rare example of a (μ-hydrido)diiron azo system, [2H] + .…”
mentioning
confidence: 99%
“…Anal. Calcd for C 28 Concentrated HCl (4.0 mL, 12 M) was added dropwise to the solution of 3 (0.5 g, 0.83 mmol) in CH 2 Cl 2 /EtOH (2 mL/15 mL). The solution turned deep red after stirred for 10 min, to which was added a few drops of saturated aqueous NH 4 PF 6 solution.…”
Section: Synthesis Of [{(L-sch 2 ) 2 N(4-no 2 C 6 H 4 )}-Fe 2 (Co) 5 mentioning
confidence: 99%
“…The rare reports on the preparation, protonation and electrochemistry of the adt-bridged diiron complexes are confined to the all-carbonyl complexes [15][16][17][18][19][20][21][22][23]. Although CO-displacement reactions of [(l-pdt)Fe 2 (CO) 6 ] by strong donor ligands, such as CN À [4,11,24,25], PR 3 [3,5,26], CNR [27,28] and N,N 0 -disubstituted-2-imidazolylidene [29,30] have been extensively studied, to the best of our knowledge, there were very few reports on the ligand modified diiron azadithiolate complexes [31][32][33].…”
Section: Introductionmentioning
confidence: 99%